2018
DOI: 10.1155/2018/6315865
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Quizalofop-Resistant Rice for Arkansas Rice Production Systems

Abstract: Due to the ongoing evolution of herbicide-resistant weeds, new technologies are needed to maintain effective levels of control. A new rice variety that will be resistant to quizalofop, an acetyl coenzyme A carboxylase-(ACCase-) inhibiting herbicide, is currently under development. With the anticipated launch of this technology in 2018, multiple experiments were conducted to determine effectiveness of the quizalofop-resistant rice system for common grass weed species found in Arkansas rice production. One hundr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 16 publications
1
22
0
2
Order By: Relevance
“…As for the bentazon, the opposite effect of increasing the dose was verified, resulting in a higher dry weight compared to the 37.5 g ha -1 dose (Table 4). The high efficiency of the quizalofop-p-ethyl (80 g ha -1 ) on the barnyardgrass was validated by Lancaster et al (2018), where excellent controlling levels (> 92%) were observed for the 126 evaluated biotypes.…”
Section: Barnyardgrassmentioning
confidence: 96%
See 1 more Smart Citation
“…As for the bentazon, the opposite effect of increasing the dose was verified, resulting in a higher dry weight compared to the 37.5 g ha -1 dose (Table 4). The high efficiency of the quizalofop-p-ethyl (80 g ha -1 ) on the barnyardgrass was validated by Lancaster et al (2018), where excellent controlling levels (> 92%) were observed for the 126 evaluated biotypes.…”
Section: Barnyardgrassmentioning
confidence: 96%
“…Amid the main infesting-weed species of the irrigated rice are the weedy rice (Oryza sativa) and the barnyardgrass (Echinochloa spp.) (Lancaster et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Acetyl CoA carboxylase-resistant rice allows POST applications of quizalofop to control troublesome grass weed species in rice (Epp et al 2016;Rustom et al 2018). Lancaster et al (2018) reported that quizalofop controlled barnyardgrass >96% at the two-to three-leaf growth stage and >90% at the five-to six-leaf growth stage in ACCase-resistant rice. Webster et al (2019) reported that quinclorac and triclopyr antagonized barnyardgrass control 28 d after application when mixed with quizalofop at 120 g ha −1 .…”
Section: Grass Studymentioning
confidence: 99%
“…ArOPPs are relatively new class of selective herbicides prepared from heterocyclic oxyphenoxy propionic acid derivatives for the control of graminaceous weeds in broad-leaved crops and tolerant cereal crops [4]. They are applied mainly on cotton, soybeans and sugar beet as well as in the wheat, corn, barley, rye, legumes, sunflowers, sesame, alfalfa, peanuts, lettuce, spinach, potatoes, cucumber, peas, tomatoes, fennel, and strawberries [5][6][7][8]. ArOPPs are post-emergence (PoEm) herbicides composed of about fifteen members.…”
Section: Introductionmentioning
confidence: 99%